Impact of Individual Patient Profiles on Adherence to Guideline Directed Medical Therapy in Heart Failure With Reduced Ejection Fraction: VCOR-HF Study. - Driscoll, Andrea; Dinh, Diem; Wong, James; Hopper, Ingrid; Mariani, Justin; Zimmet, Hendrik; Brennan, Angela; Lefkovits, Jeffery; Carruthers, Harriet; Reid, Christopher (2020)
BACKGROUND: Multiple co-morbidities complicate initiation of medical therapy in patients with heart failure with reduced ejection fraction (HFrEF). Adherence to guidelines based on individual patient profiles is not well described. This paper examines the effect of individual patient profiles on guideline recommended therapies for HFrEF.